TINJAUAN HUKUM TERHADAP PELAKSANAAN PENERAPAN SERTIPIKAT HAK ATAS TANAH SECARA ELEKTRONIK DI KABUPATEN MUNA BARAT: STUDI PADA KANTOR PERTANAHAN MUNA BARAT - Muskur La Ode Muhammad; Fatahillah As L.M (Fakultas Hukum Universitas Dayanu Ikhsanuddin, 2026)
The objectives that the author wishes to achieve in this study are to how is the implementation of electronic cadastral certificates going at West Muna Land Office? What are the obstacles in the implementation of electronic cadastral certificates at West Muna Land Office? This research is part of the typology of empirical legal research. Research data were collected through document/library research and interview switch West Muna Land Agency Office and then processed using a qualitative descriptive program. The results are presented through conclusions and statements. The analysis was carried out using a legislative approach combined with a sociological approach. The results of this study have shown that the implementation of the application of electronic cadastral certificates at the National Land Agency in West Muna Regency should be implemented, taking into account the implementation of electronic cadastral certificates to make it practical, cost-effective and time. Efficient both for the land registry officials in West Muna and the community, especially West Muna, and to overcome problems related to the land sector such as duplicate certificates or to reduce corruption, collusion and nepotism. Weaknesses in the implementation of electronic cadastral certificates at the National Land Agency in West Muna Regency are Human Resources (HR) readiness, data validation not completed, land registry not completed, lack of existing facilities, Internet network not optimal, lack of socialization, geographical location of the area, mosh/ of the islands, reorientation/austerity.